GLOBALISASI DAN PERBUDAKAN MENURUT AL-QURAN (Analisis Tekstual dan Kontekstual) - Holilulloh, Andi; Larhzizer, Fouad (Institut Agama Islam Imam Ghozali, 2020)
Al-Quran al-karim is a book of samawi (God’s talk) which is the last book that Allah SWT has given to all muslims and it has a function as a guideline and an advice not only for arab people but also for all muslim people in the world. Al-Quran consists of all aspects about human’s life, in other hand it is suitable for all aspects on vertical and horizontal, and the relationship between human and nature is truly in the Al-Quran. Globalization is a challenge that we could not stay away, the center of information that gives a lot of advantages to all humans and also it becomes a sharp knife that could stab someone’s future especially to the students of Islamic boarding house where they face the challenge while they are living and studying Islamic education, Islamic classic books, learning to read Al-Quran. Enslavement is actually meant as public problems and it is related to the impact of globalization among us and it makes us to discuss more about this case. Hermeneutik has a role about this case to have function and to give an easy interpretation of verse of Al-Quran, it can make us easy to analyze verses what we are meaning, this study is actually around us from the past to complete all aspects in the Al-Quran, both the verses and the meanings.